Iron regulatory pathways differentially expressed during Madurella mycetomatis grain development in Galleria mellonella - Abugessaisa, Imad; Konings, Mickey; Manabe, Ri-Ichiroh; Murphy, Cathal M.; Kawashima, Tsugumi; Hasegawa, Akira; Takahashi, Chitose; Tagami, Michihira; Okazaki, Yasushi; Eadie, Kimberly; Lim, Wilson; Doyle, Sean; et al. (Nature communications, 2025)
Mycetoma is a chronic granulomatous infection of the subcutaneous tissue, most often caused by the fungal pathogen Madurella mycetomatis . Characteristic of the infection is the formation of grains. However, knowledge of the function and formation of the grain is limited. Here, we use a Galleria mellonella larvae infection model and transcriptomic profiling to identify processes associated with M. mycetomatis grain formation. Larvae were infected with M. mycetomatis and, after 4, 24, 72 and 168 h post-inoculation, RNA was extracted from larval content and sequenced. We found that 3498 G. mellonella and 136 M. mycetomatis genes were differentially expressed during infection. In particular, genes encoding proteins related to iron transport were highly expressed by both G. mellonella (transferrin and ferritin) and M. mycetomatis (SidA, SidD and SidI). LC-MS/MS analysis of M. mycetomatis cultured under iron-limiting conditions revealed the presence of SidA and SidD orthologs, and concurrent RP-HPLC and LC-MS identified a singly charged, putative siderophore in culture supernatant. Furthermore, we show that M. mycetomatis can obtain iron from holoferritin. Thus, our results highlight the importance of iron acquisition pathways during grain formation, suggesting potential avenues for development of new diagnostic and therapeutic strategies for mycetoma. Mycetoma is a chronic granulomatous infection of the subcutaneous tissue, most often caused by the fungal pathogen Madurella mycetomatis . Here, the authors show that iron acquisition pathways in both pathogen and host are upregulated during grain formation in an insect larva infection model.